Analisis Optimalisasi Perawatan Excavator Untuk Menunjang Produktivitas Unit - Luthfi Wifaqi, Ahmad Naufal; Prihadianto, Braam Delfian; Winarto, Felixtianus Eko Wismo; Harjono; Oktavian, Dicky (P3M Politeknik Negeri Cilacap, 2025)
Maintenance is an important daily activity that aims to ensure equipment or units can operate properly by reducing the risk of damage. One of the heavy equipment units used in mining projects is an excavator, but the high frequency of breakdowns in excavator units requires optimization of the maintenance that has been carried out. This study aims to analyze the performance and effectiveness of hydraulic excavator unit maintenance using the physical availability, mechanical availability, use of availability, mean time between failure, and mean time to repair calculation methods. The calculations show an 8.12% increase in the average PA, MA, and UA values and a 5.16-hour increase in MTBF. Meanwhile, the MTTR calculation results indicate a time reduction of 6.16 hours after optimization. The calculation results after optimization show that the maintenance carried out is effective and efficient to support the unit's productivity